Partial duplication of DHH causes minifascicular neuropathy: A novel mutation detection of DHH. Issue 6 (22nd May 2017) - Sato, Naoko Saito; Maekawa, Risa; Ishiura, Hiroyuki; Mitsui, Jun; Naruse, Hiroya; Tokushige, Shin‐ichi; Sugie, Kazuma; Tate, Genshu; Shimizu, Jun; Goto, Jun; Tsuji, Shoji; Shiio, Yasushi
Abstract: Minifascicular neuropathy (MN) is an extremely rare developmental malformation in which peripheral nerves are composed of many small fascicles. Only one patient with MN with 46XY gonadal dysgenesis (GD) was found to carry a mutation affecting the start codon in desert hedgehog ( DHH ). We identified an identical novel rearrangement mutation of DHH in two consanguineous families with MN, confirming mutations in DHH cause MN with 46XY GD. The patients with the 46XY karyotype developed GD, whereas a patient with the 46XX karyotype did not. These findings further support that DHH has important roles in perineural formation and male gonadal differentiation.